-Commerce Adoption In Developing Business Education Insights: A Systematic Literature Review Analysis - Purwianti, Ari; Emilia Nur Cholifah; Luthfi Nur Alifah; R Rizky Nuryanti; Andy Prasetyo Wati; Ludi Wishnu Wardana (International journal of technology and education research, 2025)
The systematic literature review (SLR) article on e-commerce adoption in developing business education insights has the following objectives; (a) Identify the role of e-commerce adoption in expanding business insights; (b) Practical integration of e-commerce in business education; (c) E-commerce skills and insights as a result of business education; (d) Recommendations for curriculum, teachers, and students adopting e-commerce in business education. The method of writing a systematic literature review (SLR) article is a literature research method sourced from the Elsevier and Emerald databases. SLR analysis uses the PRISMA method to find relevant articles in accordance with the research objectives. The results found three aspects included in the curriculum in improving business insights, namely (a) digital competencies including technical skills and technology adaptation; (b) learning digital transformation and business innovation, such as the use of e-commerce to study customer behavior; (c) digital marketing strategies to easily adapt to changes in the increasingly digital business world. The implication of this research is for the business education curriculum to adapt to the demands of an increasingly digital business world.